Model Konstruksi Kognitif Metaphora Kewirausahaan: Pendekatan Konseptual - Sulastri; Zakaria Wahab; Veronica Varbi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
Entrepreneurial knowledge is taxonomic knowledge with complex and extensive metaphors. Its complexity and breadth required constructing simplification to achieve the effectiveness of the cognitive goals that can be guided as a learning outcome. The aim of this research is to produce a conceptual model on the cognitive entrepreneurial knowledge in the learning process in higher education. The cognitive construction model is focused on important variables of entrepreneurship such as (a) opportunities recognition, (b) opportunities exploitation (c) innovation, (d) proactive, and (e) risk-taking as the main construct variable in entrepreneurship. The conceptual study concluded that to do cognitive construction from a learning process, 5 aspects are required: (1) content of what will be interpreted; (2) type of representation that will be reflected and explained; (3) referent, the background of representation of the meaning of content; (4) relatedness, the relationship between content and context and (5) the interaction between content, representation, referent and relatedness in forming intentionality. The cognitive construction process will reach it means if intentionality is formed as the goal of learning activity. The proposition of the knowledge cognitive construction model gives implications on the future empirical studies as a part of taxonomy and the body knowledge of entrepreneurship.